Prediksi Penyebab dan Solusi Ketidaknyamanan Kerja dengan Aplikasi Sistem Pakar - Chairul Saleh; Ade Trisna P. (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
Lack of attention to ergonomic factors such as attitude factor, job position, and jobdensity causes incidence uncomfortable job feeling. Hereinafter can cause accident andgenerate disease. Home industry like streets vendor process the product with special skill andcarefulness so that yield accuracy, beauty, good at measure, and according to order ofcustomer. This paper will present expert system application to detect and give solution touncomfortable job causes because of eyes strain, repetition and posture. To recognize patternpart of body along with grade of pain, cause, and solution used by artificial neural networkmethod (Back-Propagation) with trainbpx and Learning Vector Quantization. Result trainingof network obtained that to recognize cause pattern of feel pain, performance efficacytraining of trained network 99%, to recognize solution pattern of repetition cause obtained80%, hereinafter to recognize solution pattern of posture cause obtained 99%. The networkwhich have been trained can be used to predict solution and cause of uncomfortableness atdiffering case with the same variable.Keywords: expert system, neural network, back-propagation, learning vector quantization,ergonomic.